Testing strength and power in soccer players: The application of conventional and traditional methods of assessment - Paul, D. J.; Nassis, G. P. (The Journal of Strength and Conditioning Research, 2015)
Soccer is a highly complex sport influenced by many physical, psychological, tactical, and technical factors. In terms of basic physical components, strength and power are considered requisites for many important actions such as tackling, jumping, and shooting. Hence, assessment of strength and power is commonly performed within a soccer club's test battery. The objective is to use valid, reliable, and sensitive measures that allow for trustworthy analysis of the physical characteristics of players. Before any credence can be placed in test results, test's validity, reliability, and sensitivity needs to be established. This will allow practitioners to make informed decisions about test selection. This review examines the reliability, validity, and sensitivity of different strength and power assessments in soccer. The suitability of conventional and functional tests is detailed and the strengths and weaknesses of isokinetic dynamometry, hand-held dynamometry (HHD), repetition maximum, and power testing are also addressed. Generally, the tests considered in this review provide moderate to high reliability in soccer players of different training level. Similarly, the consensus demonstrates test methods to be sensitive to training interventions. In comparison, test validity seems less established. Isokinetic dynamometry has often been recognized as a gold standard measure of testing strength. Other methods of assessment are emerging as viable options (e.g., HHD), likely due to functionality and suitability of testing. Given the demands within a soccer club setting, practitioners should endeavor to use testing procedures that are informative yet not time consuming or labor intensive. By providing this, practitioners may have the option to perform more regular monitoring throughout the season rather than a limited number of specific time periods.